Identifikasi Konflik di Indonesia: Studi Terhadap Kondisi dan Pemicu Tindakan Kekerasan di Timor Timur dan Maluku-Ambon - Irfan, Muhammad (Islam & Contemporary Issues, 2022)
High socioeconomic inequality was at the basis of the conflict issues in Maluku, especially Ambon, and East Timor. where immigrants, who are typically from diverse ethnic groups, make up the majority of the economic market players. A dispute may start when it is sparked by a minor issue in a setting of extreme socioeconomic imbalance in society. When racial and religious tensions were aroused, as was the case in the aforementioned account, the violence quickly expanded. This study seeks to pinpoint the conflict's underlying causes, its contributing factors, and its impact on religion. As a result, the studies in this paper's sources were from literature reviews of books, articles, study findings, or reports of religious violence and conflict in Indonesia. The study findings from a number of institutions that directly address the problem of conflict emergence, such as the underlying causes of conflicts, triggering variables, and issues pertaining to conflict resolution techniques, are the sources of data used in this paper.